Novel variants of NEK9 associated with neonatal arthrogryposis: Two case reports and a literature review - Liu, Fang; Dai, Liying; Li, Zhi; Yin’s, Xiaowei (Frontiers in Genetics, 2023)
Objective: Pathogenic variants in NEK9 (MIM: 609798) have been identified in patients with lethal congenital contracture syndrome 10 (OMIM: 617022) and arthrogryposis, Perthes disease, and upward gaze palsy (APUG and OMIM: 614262). The shared core phenotype is multiple joint contractures or arthrogryposis. In the present study, three novel variants of NEK9 associated with neonatal arthrogryposis were reported. Methods: The clinical data of two premature infants and their parents were collected. The genomic DNA was extracted from their peripheral blood samples and subjected to trio-whole-exome sequencing (trio-WES) and copy number variation analysis. Results: Using trio-WES, a total of three novel pathogenic variants of NEK9 were detected in the two families. Patient 1 carried compound heterozygous variations of c.717C > A (p. C239*741) and c.2824delA (p.M942Cfs*21), which were inherited from his father and mother, respectively. Patient 2 also carried compound heterozygous variations of c.61G > T (p. E21*959) and c. 2824delA (p. M942Cfs*21), which were inherited from his father and mother, respectively. These variants have not been previously reported in the ClinVar, HGMD, or gnomAD databases. Conclusion: This is the first report about NEK9-related arthrogryposis in neonatal patients. The findings from this study suggest that different types of mutations in NEK9 lead to different phenotypes. Our study expanded the clinical phenotype spectrum and gene spectrum of NEK9-associated arthrogryposis.